2013
DOI: 10.1007/s10059-013-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Mitochondrial Dysfunction by Poly(ADP-Ribose) Polymer: Implication for Neuronal Cell Death

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) mediates neuronal cell death in a variety of pathological conditions involving severe DNA damage. Poly(ADP-ribose) (PAR) polymer is a product synthesized by PARP-1. Previous studies suggest that PAR polymer heralds mitochondrial apoptosis-inducing factor (AIF) release and thereby, signals neuronal cell death. However, the details of the effects of PAR polymer on mitochondria remain to be elucidated. Here we report the effects of PAR polymer on mitochondria in cells in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Since cytochrome C and AIF are released from mitochondria to the cytosol during mitochondrial damage, 32,41 these results were consistent with mitochondrial dysfunction. Carnosine potently inhibited the release of AIF and cytochrome C, demonstrating its protective activity on mitochondrial damage (Fig.…”
Section: Resultssupporting
confidence: 59%
“…Since cytochrome C and AIF are released from mitochondria to the cytosol during mitochondrial damage, 32,41 these results were consistent with mitochondrial dysfunction. Carnosine potently inhibited the release of AIF and cytochrome C, demonstrating its protective activity on mitochondrial damage (Fig.…”
Section: Resultssupporting
confidence: 59%
“…Anticancer drugs may induce mitochondrial dysfunction in cells via dissipation of ΔΨm leading to liberation of numerous cell death proteins from the mitochondria (24). Therefore, it was reported that the intrinsic pathway depends on the dysfunction of the mitochondria resulting from an increase in the ratio of Bak:Bcl-2 which is caused by anticancer drugs thus leading to AIF and Endo G release from the mitochondria before inducing apoptosis (25)(26)(27) which is termed caspase-independent pathways or alternatively causing cytochrome c release, activation of caspase-9 and -3 resulting in apoptosis termed the caspase-dependent pathway (28). Our results showed that DMC induced mitochondrial dysfunction (decreased levels of ΔΨm) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, it did not provide any neuronal protection as assessed by PI labeling (n ¼ 17, p ¼ 0.173, Supplemental Figure 5b). Thus, it seems unlikely that PARP contributes to cell death in this thrombin-induced ex vivo model.…”
Section: Ep3r Inhibition Improves Neuronal Survival In Organotypic Himentioning
confidence: 93%